2012
DOI: 10.1021/ol203101s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6-Substituted 6-Nitroperhydro-1,4-diazepines via Novel Tandem Retro-Henry and Mannich/Michael Reactions

Abstract: N,N'-Dibenzyl-6-hydroxymethyl-6-nitroperhydro-1,4-diazepine was converted into a nitronate via retro-Henry reaction, followed by either Michael reaction with several acrylic derivatives or Mannich reaction with different amines, thus leading to 6-substituted 6-nitroperhydro-1,4-diazepines. The tandem retro-Henry/Mannich reaction was also carried out using benzylamine as base, solvent, and reagent at the same time. Selective hydrogenation of the nitro group and complete hydrogenolysis were also successfully ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In 2009, Tei et al reported a high-yielding synthesis of 6-nitroperhydro-1,4-diazepines 30 via a double-nitro-Mannich reaction between N , N ′-dibenzylethylenediamine ( 31 ), formaldehyde, and 2-nitroethanol (Scheme ) . The same group later demonstrated that further functionalization of these products could be achieved via a base-mediated retro-Henry/nitro-Mannich reaction to form β-nitroamines 32 in moderate to good yields …”
Section: Early Developmentsmentioning
confidence: 99%
“…In 2009, Tei et al reported a high-yielding synthesis of 6-nitroperhydro-1,4-diazepines 30 via a double-nitro-Mannich reaction between N , N ′-dibenzylethylenediamine ( 31 ), formaldehyde, and 2-nitroethanol (Scheme ) . The same group later demonstrated that further functionalization of these products could be achieved via a base-mediated retro-Henry/nitro-Mannich reaction to form β-nitroamines 32 in moderate to good yields …”
Section: Early Developmentsmentioning
confidence: 99%
“…The H 4 AAZTA‐C 2 ‐COOH and H 4 AAZTA‐C 4 ‐COOH ligands are the derivative of H 4 AAZTA in which the methyl group is substituted by n ‐propionic and n ‐valeric acid pendants (Scheme 1) for conjugation purposes [15, 16] . Generally, three N and four carboxylate O atoms can simultaneously bind the metal ion in the AAZTA complexes [17–22] .…”
Section: Resultsmentioning
confidence: 99%
“…Compound 4 a was successfully obtained over five steps, starting from the synthesis of hydroxymethyl diazepine ( 1 a ) by double nitro‐Mannich reaction between N , N ′‐dibenzylethylenediamine, paraformaldehyde, and 2‐nitroethanol. Then, compound 1 a was reacted with tert ‐butyl acrylate and t BuOK in THF, by tandem retro‐Henry and Michael reactions, [16] to afford compound 2 a in good yield. Hydrogenolysis using palladium on carbon and H 2 and subsequent alkylation with methyl bromoacetate yielded the compound 3 a .…”
Section: Resultsmentioning
confidence: 99%